Determinan Ekspor Di Indonesia - Fanny Septina* (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2020)
ABSTRACTThis study aims to explore macroeconomic factors that affect non-oil and gas exports in Indonesia. The research data are non-oil and gas export data, Gross Domestic Product, inflation, US dollar exchange rate, foreign direct investment in the 2010-2019 period published by Bank Indonesia statistics. The research method uses the Vector Error Correction Model (VECM) analysis with the Augmented Dickey Fuller (ADF) stationary test, Johansen's cointegration test, Granger causality test, Error Correction Model. The results showed there was a cointegration relationship between all dependent and independent variables, a direct relationship with the US dollar exchange rate and inflation on Gross Domestic Product, Gross Domestic Product on exports. In the short term Gross Domestic Product, inflation, exchange rates, and foreign direct investment have no significant effect on non-oil and gas exports. In the long run, Gross Domestic Product has a significant effect on non-oil and gas exports.Keywords: non-oil export, macroeconomy, cointegration, causality, error correction model